Desertification-Climate Change Interactions - Mexico's Battle Against Desertification - Aguirre-Salado, Carlos Arturo; Treviño-Garza, Eduardo Javier; Aguirre-Calderón, Oscar Alberto; Jiménez-Pérez, Javier; González-Tagle, Marco Aurelio; Valdez-Lazalde, José René (IntechOpen, 2012)
None